Functional Attachment in Kuching Riverfront Promenade, Sarawak - Malaysia - Bambang, Karsono; Atta Idrawani, Zaini; Awang Hasim, Awang Sulong; Siti Halipah, Ibrahim; Azhaili, Baharun (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
The relationship between people and certain places can stimulate the sense of place, this process is recognized as place attachment. Place attachment also indicates the relationship between physical image and its function, through this process the sense of a place can be established. These concepts focus on the physical elements and activities together with the meanings influenced by users that will create the identity and the meaning of the place. Allowing for this issue, the research examines the functional attachment which will affect the level of attachment in Kuching Riverfront Promenade (KRP), a popular public space among local people. By using indirect method to simplify common patterns and human-specific patterns of the place, this research covers subject of place attachment. Questionnaire survey were led to a certain area of the promenade with an overall of 165 respondents and 18 stall operators were interviewed. The findings point out that the respondents have a strong association with the local environment and designate the importance of place as economics’ dependence and recreational place. The level of functional attachment to KRP is between level 1 to level 4. Measuring at level 4 involves a higher commitment in loyalty, goals and obedience to the environment.